Єврейське кладовище в Борисполі (за експедиційними матеріалами Марії Вязьмітіної та Марії Новицької 1924 року) - Ходак, І.О. (Сіверщина в історії України, 2021)
Дослідження єврейської культурної спадщини в Україні з огляду на вагомі втрати пам’яток упродовж совєтського періоду спонукає чималу увагу приділяти історії вивчення питання. У статті систематизовано та розширено вербальні відомості про надгробки на єврейському кладовищі в Борисполі, зафіксовані в доповіді М. Вязьмітіної і М. Новицької (1924), підготовленій під час одноденної навчальної екскурсії (експедиції) студентів Київського археологічного інституту під орудою Д. Щербаківського. На основі власних натурних спостережень, а також прорисовок і малюнків, виконаних учасниками експедиції, авторки класифікували надгробки за конструкцією, виділивши чотири основні типи й кілька підгруп у межах першого з них, а також зафіксували характер орнаментального оздоблення з урахуванням іконографії та семантики мотивів, техніки виконання. Research of the Jewish culture heritage in Ukraine, given considerable loss of sights and monuments in the Soviet time, encourages to pay a lot of attention to the history of studying this issue. The article has systematized and significantly extended information about the tombstones of a Jewish cemetery in Boryspil, which can be found in Mariia Viazmitina and Mariia Novytska’s report titled «Jewish Cemetery in Boryspil» (1924) based on the results of a 1-day educational excursion (expedition) that the students of Kyiv Institute of Archaeology under the guidance of Danylo Shcherbakivskyi had. Following their personal field observations, along with trace drawings and sketches made by the expedition participants, the report authors classified the tombstones by design having singled out four major types and several sub-groups within the first major type, and also documented the features of ornamental decoration with due consideration of iconography and symbolism of motives, execution techniques. They noted that vertical stone slabs with inscriptions and ornamental compositions were the least widespread type of tombstones in the Boryspil cemetery. Most frequently met tombstones were the ones similar to small buildings made of brick (sometimes plastered), stone, wood, covered with metal or timber; a bit less frequently – high and thick wooden boards having inscriptions and ornaments from time to time; and the most recent monuments were made of gray stone and shaped as a tree stem with trimmed branches. It is noteworthy that the young researchers went beyond solely analyzing the design, technology and ornament parameters of the Boryspil cemetery tombstones – and presented the equivalents from Jewish cemeteries in Odessa and Kyiv, which fact further speaks to their interest in the issues under study. The archive materials prove that at least Mariia Novytska alone kept on documenting the Jewish art monuments in 1920s, principally the tombstones in the regions of Eastern Podillшa, Katerynoslavschyna and Crimea.